INFORMATIZATION AND MANAGEMENT OF SCIENTIFIC RESEARCH: PUBLICATION ACTIVITY RATING ALGORITHM - LIKHONOSOVA, GANNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article updates the problem of the feasibility of developing a software system designed to help heads of research groups, as well as individual researchers, make decisions about improving publication activity, scientometric performance, identify weaknesses and strengths, directions, and specific solutions in the form of automated recommendations for increasing the value and representativeness of scientometric indicators . The research is based on the use of the theory of system analysis, which allows a comprehensive consideration of all aspects related to the processes of finding ways between static and dynamic aspects of publishing activity. The method of building a publication rating based on profiles of scientists in Scopus is characterized. In the course of the study, it was shown that it is currently appropriate to develop a software system designed to help heads of research groups, as well as individual researchers, make decisions about improving publication activity, scientometric performance, identify weaknesses and strengths, directions, and specific decisions in the form of automated recommendations for increasing the value and representativeness of scientometric indicators. The proposed technique, including the algorithm for collecting, refining and ranking scientometric data is the basis of the methodological toolkit for the analysis and assessment of publication activity. The practical significance of the obtained scientific results lies in the proposal of approaches and algorithms, on the basis of which it is possible to develop a software system designed to help heads of research groups, as well as researchers to make decisions on increasing publication activity, scientometric performance, identify weaknesses and strengths, directions and specific solutions in the form of automated recommendations for increasing the value and representativeness of scientometric indicators.
Keywords: informatization; scientific research; rating; decision support system construction algorithm; individual scientometric indicators